2018
DOI: 10.1016/j.envsci.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Resilient futures of a small island: A participatory approach in Tenerife (Canary Islands) to address climate change

Abstract: HighlightsStakeholders and citizens were engaged in a participatory process.Climate change adaptation frame is too narrow for small island contexts.Resilience is a helpful framing to discuss strategies to tame hazardous events.Resilience was defined as energy, food and water sovereignty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…For example, it has been alleged to be meaningful to evaluate the statu quo of adaptation planning and the understanding of existing policies and barriers ( Hernandez et al, 2018a ). Consequently, public participation prepares the conditions for long term climate goals formulation and visions ( Hernandez et al, 2018b ; Hilden et al, 2017 ; Mendizabal et al, 2018 ). Similarly, citizen participation is said to reinforce the government’s ability to attain the goals established ( Larsen et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been alleged to be meaningful to evaluate the statu quo of adaptation planning and the understanding of existing policies and barriers ( Hernandez et al, 2018a ). Consequently, public participation prepares the conditions for long term climate goals formulation and visions ( Hernandez et al, 2018b ; Hilden et al, 2017 ; Mendizabal et al, 2018 ). Similarly, citizen participation is said to reinforce the government’s ability to attain the goals established ( Larsen et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, there seems to be a poor commitment from public administrations towards public participation on the definition of an adequate CC adaptation strategy that should be based on deep participatory discussions (Hernandez et al, 2018). However, the engagement process carried out in this case study showed that several social actors declined to participate when invited.…”
Section: Discussionmentioning
confidence: 99%
“…The population clearly recognises the need for a transition towards more sustainable land management models, however, the need to relocate uses and activities situated in vulnerable sectors is not accepted. The scarce participation of the population in decision making is being reverted by providing incentives for more participative risk management processes, examples of which are occurring in other European islands such as Tenerife or The Isles of Scilly (Hernández et al, 2018;Petzold, 2018). The decision on adaptation strategies follows a pattern imposed by the administration (top-down), in which community participation has not been adequately promoted.…”
Section: No 9 Sustainable Use Of Land and Nature-based Solutions Pamentioning
confidence: 99%
“…In the specific case of island territories, these variables compromise the resilience of their functional structures (Aswani, 2015;Lazrus, 2012). Some islands, as limited territories, are becoming places for experimentation on alternative planning tools in the face of climate change (Depraetere, 2008;Gagliardi, 2009, p. 47;Hernández et al, 2018) in combination with sustainable development (Chapman, 2011). Critical nodes on the world scale such as small islands (King, 2009, p. 77) are ideal places for comparative exploration of local-scale development strategies for their later projection at an international scale.…”
Section: Introductionmentioning
confidence: 99%